2018
DOI: 10.1186/s12939-018-0785-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the complex relationships among actors involved in the implementation of public-private mix (PPM) for TB control in India, using social theory

Abstract: BackgroundPublic Private Partnerships (PPP) are increasingly utilized as a public health strategy for strengthening health systems and have become a core component for the delivery of TB control services in India, as promoted through national policy. However, partnerships are complex systems that rely on relationships between a myriad of different actors with divergent agendas and backgrounds. Relationship is a crucial element of governance, and relationship building an important aspect of partnerships. To und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…This is consistent with examples from PPP in the Asia Pacific focussed on adult health where private providers had access to free essential medicines and diagnostics, access to training and supervision, and branding to align the provider with the national program and generate demand. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] This is also consistent with approaches more globally. [39] By contrast, incentives for the public sector were often less well articulated and/ or more altruistic (improved services for adolescents), but identifying these benefits were nonetheless important to ensuring enhanced partnership.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with examples from PPP in the Asia Pacific focussed on adult health where private providers had access to free essential medicines and diagnostics, access to training and supervision, and branding to align the provider with the national program and generate demand. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] This is also consistent with approaches more globally. [39] By contrast, incentives for the public sector were often less well articulated and/ or more altruistic (improved services for adolescents), but identifying these benefits were nonetheless important to ensuring enhanced partnership.…”
Section: Discussionsupporting
confidence: 82%
“…Many of the issues emerging from the FGDs have been documented previously also. [78] The joint monitoring mission conducted in 2009 and 2012 have shown that delays and nonpayment of reimbursements for the implementation of schemes prompted private practitioners to stay away from signing any new schemes. In addition, only 4% of the state's allocation is for PPM, and out of this only one-third is being actually spent.…”
Section: Discussionmentioning
confidence: 99%
“…Also, due to a lack of funding and resources, the majority of NGOs in India have problems delivering equitable and equal health care services to the poor. NGOs have to wait for a long time to receive their payments, which decreases their motivation to work with the government [68][69][70] . However, we need to be cautious on the politics of NGOs and their functioning.…”
Section: Nongovernment Organizations and Public Health Care In Indiamentioning
confidence: 99%